2015
DOI: 10.1016/j.brs.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Access to the Vagus Nerve Central Projections via Electrical Stimulation of the External Ear: fMRI Evidence in Humans

Abstract: Background Tract-tracing studies in cats and rats demonstrated that the auricular branch of the vagus nerve (ABVN) projects to the nucleus tractus solitarii (NTS); it has remained unclear as to whether or not the ABVN projects to the NTS in humans. Objective To ascertain whether non-invasive electrical stimulation of the cymba conchae, a region of the external ear exclusively innervated by the ABVN, activates the NTS and the “classical” central vagal projections in humans. Methods Twelve healthy adults und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
579
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(622 citation statements)
references
References 53 publications
32
579
2
9
Order By: Relevance
“…In an influential study, Fallgatter et al (2003) stimulated the tragus and showed that active tVNS, compared to sham, produced a clear and reliable vagus sensory evoked potential in healthy participants. Further, two functional magnetic resonance imaging (MRI) studies in healthy humans have found that tVNS increased activation in the brainstem region including the locus coeruleus (LC) and nucleus of the solitary tract, indicating that tVNS is able to effectively stimulate vagal afferents to the brainstem (Dietrich et al 2008;Frangos et al 2015). In rats, it has been shown that VNS leads to an intensity-dependent increase in brain norepinephrine (NE) in response to stimulation of the left vagus nerve (Raedt et al 2011;Roosevelt et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In an influential study, Fallgatter et al (2003) stimulated the tragus and showed that active tVNS, compared to sham, produced a clear and reliable vagus sensory evoked potential in healthy participants. Further, two functional magnetic resonance imaging (MRI) studies in healthy humans have found that tVNS increased activation in the brainstem region including the locus coeruleus (LC) and nucleus of the solitary tract, indicating that tVNS is able to effectively stimulate vagal afferents to the brainstem (Dietrich et al 2008;Frangos et al 2015). In rats, it has been shown that VNS leads to an intensity-dependent increase in brain norepinephrine (NE) in response to stimulation of the left vagus nerve (Raedt et al 2011;Roosevelt et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study was able to observe a widespread activation of the NTS by cymbal conchae stimulation in human. However, the parameters used for brainstem analysis were insufficiently conservative (33). In contrast, we used highly conservative parameters (18) and consequently the number and size of the activated areas are robust.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the LC block the anti-epileptic and anti-depressant effects of VNS (Krahl et al, 1998). VNS increases firing rates of LC neurons and norepinephrine concentrations in the cortex and hippocampus, two projection sites of the LC (Dorr & Debonnel, 2006;Roosevelt et al, 2006) and activates the LC in a fMRI study in humans (Frangos et al, 2015). VNS may act initially and/or predominantly on the LC, and indirectly with the dorsal raphe nucleus via afferents from the LC (Dorr & Debonnel, 2006).…”
Section: Vagus Nerve Stimulation In Epilepsy and Depressionmentioning
confidence: 97%
“…Devices stimulating the VN at the cervical level or at the auricular level have been developed. Indeed, the cymba concha of the external ear is innervated by a sensory auricular branch of the VN (Peuker & Filler, 2002) that sends projection in the NTS in cats (Nomura & Mizuno, 1984) and humans (Frangos et al, 2015). Transauricular (ta) VNS could thus activate the CAP through an inflammatory reflex.…”
Section: Noninvasive or Invasive Vns?mentioning
confidence: 99%